Detection of Cholesterol Oxidation Products (COPs) in raw and chilled storage of chicken sausages formulated with chicken fat and red palm mid fraction - Alina A.R.; Fahmi M.I.; Hashari S.Z.; Thema Juhana M.J.; Juriani J.; Siti Mashitoh A. (2024)
Indexed by Scopus